Pharmacologic activation of hepatic farnesoid X receptor prevents parenteral nutrition–associated cholestasis in mice. Issue 2 (7th December 2021) - El Kasmi, Karim C.; Ghosh, Swati; Anderson, Aimee L.; Devereaux, Michael W.; Balasubramaniyan, Natarajan; D'Alessandro, Angelo; Orlicky, David J.; Suchy, Frederick J.; Shearn, Colin T.; Sokol, Ronald J.
Abstract: Background and Aims: Parenteral nutrition (PN)–associated cholestasis (PNAC) complicates the care of patients with intestinal failure. In PNAC, phytosterol containing PN synergizes with intestinal injury and IL‐1β derived from activated hepatic macrophages to suppress hepatocyte farnesoid X receptor (FXR) signaling and promote PNAC. We hypothesized that pharmacological activation of FXR would prevent PNAC in a mouse model. Approach and Results: To induce PNAC, male C57BL/6 mice were subjected to intestinal injury (2% dextran sulfate sodium [DSS] for 4 days) followed by central venous catheterization and 14‐day infusion of PN with or without the FXR agonist GW4064. Following sacrifice, hepatocellular injury, inflammation, and biliary and sterol transporter expression were determined. GW4064 (30 mg/kg/day) added to PN on days 4–14 prevented hepatic injury and cholestasis; reversed the suppressed mRNA expression of nuclear receptor subfamily 1, group H, member 4 ( Nr1h4 )/FXR, ATP‐binding cassette subfamily B member 11 ( Abcb11 )/bile salt export pump, ATP‐binding cassette subfamily C member 2 ( Abcc2 ), ATP binding cassette subfamily B member 4( Abcb4 ), and ATP‐binding cassette subfamily G members 5/8( Abcg5/8 ); and normalized serum bile acids. Chromatin immunoprecipitation of liver showed that GW4064 increased FXR binding to the Abcb11 promoter. Furthermore, GW4064 prevented DSS‐PN‐induced hepatic macrophage accumulation, hepatic expression of genes associated with macrophage recruitment and activation ( ll‐1b, C‐C motif chemokine receptor 2, integrin subunit alpha M, lymphocyte antigen 6 complex locus C), and hepatic macrophage cytokine transcription in response to lipopolysaccharide in vitro. In primary mouse hepatocytes, GW4064 activated transcription of FXR canonical targets, irrespective of IL‐1β exposure. Intestinal inflammation and ileal mRNAs ( Nr1h4, Fgf15, and organic solute transporter alpha) were not different among groups, supporting a liver‐specific effect of GW4064 in this model. Conclusions: GW4064 prevents PNAC in mice through restoration of hepatic FXR signaling, resulting in increased expression of canalicular bile and of sterol and phospholipid transporters and suppression of macrophage recruitment and activation. These data support augmenting FXR activity as a therapeutic strategy to alleviate or prevent PNAC.